2014
DOI: 10.1111/jac.12060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl on Root Growth and Cell Wall Composition of Two Soya bean Cultivars with Contrasting Salt Tolerance

Abstract: Our objectives were to determine the influence of salinity on root cell wall composition in soya beans and the possible mechanism of salt tolerance. Two soya bean cultivars, Touzan 69 (salt sensitive) and Dare (salt tolerant), were selected as experimental material for comparison. Root growth was clearly inhibited by salinity in both cultivars, but Touzan 69 showed more severe reductions in root length than Dare. In the 0–5 mm root segment (from root tip), the total cell wall sugar content of Touzan 69 decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…Cell wall, as a physical barrier surrounding the plant cell, is intimately involved in plant responses to the external environments through changes in its architecture and composition. And some studies reveal that salt stress affects cell walls severely, including the rigidity and composition [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall, as a physical barrier surrounding the plant cell, is intimately involved in plant responses to the external environments through changes in its architecture and composition. And some studies reveal that salt stress affects cell walls severely, including the rigidity and composition [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study with wheat seedlings comparing a drought sensitive with a tolerant line also showed more pectins in the tolerant cultivar, especially in young seedlings (Konno et al, 2008 ). A comparison of the cell wall composition of root tips from two soybean cultivars showed far higher levels of pectins in the salt tolerant cultivar than in the sensitive line, suggesting that the higher pectin content is beneficial for root growth under salt stress conditions (An et al, 2014 ). Older plant material from two wheat cultivars with different salt tolerance was compared by Uddin et al ( 2013 ).…”
Section: Changes In Cell Wall Composition Caused By Abiotic Stressmentioning
confidence: 99%
“…In roots, AtPAE4 expression was slightly overexpressed in response to salt stress as was AtPAE8. A comparison of the CW composition in root tips from soybean (Glycine max) cultivars with different degrees of tolerance to salt stress showed more pectin deposition in the tolerant cultivar as compared with the sensitive line, suggesting that a higher accumulation of pectins in roots is beneficial for root growth in soils with high levels of salinity [115,116]. Shen et al, (2014) found that Arabidopsis plants which undergo salt acclimation could promote extensive remodeling of the CW, thus, priming and enforcing plants to be ready for subsequent salt stress [117].…”
Section: Cell Wall Remodeling Under Salinity Stressmentioning
confidence: 99%